2012
DOI: 10.1093/bioinformatics/bts004
|View full text |Cite
|
Sign up to set email alerts
|

Estimating abundances of retroviral insertion sites from DNA fragment length data

Abstract: A likelihood function is proposed for the discrete lengths observed in each of a collection of insertion sites and is maximized with a hybrid expectation-maximization algorithm. Patient data illustrate the method and simulations show that relative abundance can be estimated with little bias, but that variation in highly abundant sites can be large. In replicated patient samples, variation exceeds what the model implies-requiring adjustment as in Efron (2004) or using jackknife standard errors. Consequently, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(134 citation statements)
references
References 28 publications
2
131
1
Order By: Relevance
“…The clonal repertoire reflected at this sequencing depth, however, is not exhaustive, partly because of the limitations imposed by the use of a given specific restriction enzyme (Harkey et al, 2007;Gabriel et al, 2009;Wu et al, 2013) and partly because of sampling issues. Moreover, the LM-PCR method can be skewed, as can any method that employs PCR amplification of intermediate products, toward amplification of smaller PCR products, among other limitations (Berry et al, 2012;Bystrykh et al, 2012), although we could not show that small amplicons had an effect on the extent to which the pyrosequencing reads correlate with the qPCR data ( Supplementary Fig. S3).…”
Section: Typical Pcr Parameters Do Not Explain the Inconsistency Of Tmentioning
confidence: 75%
“…The clonal repertoire reflected at this sequencing depth, however, is not exhaustive, partly because of the limitations imposed by the use of a given specific restriction enzyme (Harkey et al, 2007;Gabriel et al, 2009;Wu et al, 2013) and partly because of sampling issues. Moreover, the LM-PCR method can be skewed, as can any method that employs PCR amplification of intermediate products, toward amplification of smaller PCR products, among other limitations (Berry et al, 2012;Bystrykh et al, 2012), although we could not show that small amplicons had an effect on the extent to which the pyrosequencing reads correlate with the qPCR data ( Supplementary Fig. S3).…”
Section: Typical Pcr Parameters Do Not Explain the Inconsistency Of Tmentioning
confidence: 75%
“…13,17,35 Recently, random DNA shearing by sonication and count of shear site was introduced and appear to have better accuracy and sensitivity. 20,21,23,28,36,37 We further improved this method by minimizing the number of exponential PCR cycles used for template generation and by including an internal control sample with a relatively high number of quantitatively defined VIS. The internal control allowed us to define the sensitivity, accuracy, and overall quality of each MiSeq run, and provides a standard for measuring clonal abundance in complex samples.…”
Section: Discussionmentioning
confidence: 99%
“…While our data support the use of shear site counts in place of read counts, shear site counts could potentially underestimate the absolute abundance of a relatively large dominant clone because the number of different shear sites for a given VIS could be limited by the length of sheared DNA fragments. 21 Therefore, the gold standard for measuring the frequency of dominant clones should remain being VIS-specific qPCR using primers specific for a given insertion site. 18,38 Alternatively, random barcoding could be built into the adaptor to enhance the quantitativeness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to measure the relative abundance of each integration, we quantified the number of sonication breakpoints for each site. Previous studies have shown that sonication breakpoints can be used as a measure of clonal expansion; if an integration has more than one breakpoint, the cell carrying that integration has undergone clonal expansion (43).…”
Section: Characterization Of Alv-j Isolate Pdrc-59831mentioning
confidence: 99%